NILAI SUFISTIK DALAM PROSEDUR SELF HEALING - Ajeng Pertiwi Rahmawati; Cucu Setiawan; Naan Naan (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
Sufistic studies seem to be of particular interest to contemporary Indonesian society. As the development of science, Sufistic studies were felt in the field of psychotherapy. In fact, in 2016 psychotherapy sufism experts contributed to developing a therapeutic technique called Mind Healing Technique (MHT) discovered by Ahmad Jais Al-Sambasy. One type of therapy in MHT is self healing therapy. Therefore, this study aims to find out how the procedure of implementing selfhealing in the 13th MHT Training in Bandung. In addition, it is also to find out whether Sufitic values are contained in the self healing procedure. While the type of research methodology used is descriptive qualitative method. The techniques used in data collection are observation techniques with the type of participatory observation, interviews using the type of semi-structured interviews, and documentation techniques in the form of data collection related to news writing, journal articles, and video coverage. So from the results of the research that has been carried out there are seven steps in the self healing procedure. 1) Condition the body position 2) Adjust the rhythm of the breath 3) Relax - focus - surrender 4) Pray 5) RTD + positive pin 6) Adjust the rhythm of the breath 7) Say thank you. While the Sufistic values contained in the form of patient values, resignation values, resignation values, the concept of takhalli and tahalli, rida values and values of gratitude. In the research process the writer found new information about the istigfar method in self healing therapy, and in that method contained an additional value in the form of repentance value.